Prospecção de genes associados ao processo de floração em tomateiro. - Ferreira, Daiane Cristina Cabral (2008)
Flowering is a process marked by switch of shoot apical meristem to floral meristem, and it involves a complex regulation by endogenous and environmental factors. Analyses of key flowering genes have been carried out primarily in Arabidopsis thaliana and have provided a foundation for understanding the underlying molecular genetic mechanisms controlling different aspects of floral development. Several homologous have been found in other species, but for crops species such as tomatoes this process is not well known. The aim of this work was to use the genetic natural variation associated to the flowering process and use molecular tools such as subtractive libraries and real time PCR in order to identify and analyze the expression from genes that may be associated to flowering in these two species: L. esculentum cv Micro-Tom and L. pimpinellifolium. Our results showed there were identified many genes related to vegetative and possibly to the flowering process. There were also identified many sequences that were unknown. We ve chosen three genes to analyze the expression by real time PCR. The histone H2A gene gave an expression higher in L. pimpinellifolium, due to this the expression of this gene may be associated to flowering in this specie. It was also analyzed the expression of an unknown gene that might be a key factor of the transition to flowering, also in L. pimpinellifolium. For the elongation factor 1-α expression, the expression results were not informative, so this gene may have a constitutive expression in vegetative and flowering state. The results observed allowed us to identify possible genes that may be related to the flowering process. For further results it will be necessary a better characterization of them.